The Sunggal War 1872-1895: In Search of East Sumatera Local Wisdom - Suprayitno Suprayitno; Farida Hanum Ritonga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The Sunggal War that occurred from 1872 to 1879 was the first war of the people against Dutch’s colonialism in North Sumatera. This war was started by then Sultan Deli who gave away land concession that belongs to the leaders of Sunggal to the Dutch farming company. This enraged these leaders and started a war listed in colonial archive as “Batak Oorlog”. Historical references of the Sunggal War from Erwiza Erman, Luckman Sinar, Ratna and others are not sufficient enough in addressing local leadership issues in Sunggal in leading the army, as well as how it affects the economy and land owning pattern in East Sumatera which was the primary cause of war. The Sunggal leaders also managed to tie a coalition with the local ethnicity, among them were the Hai, Malay, Aceh and Gayo. As a result, the Dutch were forced to build the Labuhan Deli port to ease their army’s activity in winning the war. In turn, Labuhan Deli had become the main contributor to East Sumatera’s economic growth. The Sunggal War also gave good experience on how to handle land owning issues in the eastern prefecture. This article is a research financed by Research Board USU/BP-PTN 2016. Historical methods were used in the colonial archive in ANRI through economical and conflict approach. The issue is addressed in this article in search for local’s wisdom and orally transmitted knowledge of the Sunggal War, particularly on the traditional leadership and conflict management in Deli, East Sumatera.